Proceedings of the 4th Teaching &Amp; Education Conference, Venice 2017
DOI: 10.20472/tec.2017.004.001
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Smartphone for Learning Activities by University Students in Kuwait

Abstract: Abstract:There has been a shortage of relevant studies concerning Smartphone usage in Kuwait by people in general and students in particular. The aim of this study was therefore twofold: (i)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
(2 reference statements)
4
8
0
1
Order By: Relevance
“…This suggests that the use of mobile technology has a statistically significant impact on the instructional activities of physics instructors and students during the COVID-19 lockout, as well as students' attitudes toward academic activity. The findings are consistent with those of Alzougool and Almansour [17] , who discovered that using a mobile device benefited both students and instructors. The findings were also consistent with those of Iqbal and Bhatti [18] and Onyema et al [19] , who discovered that mobile phones have interesting features that are appealing to learning.…”
Section: Regression Analysis and Interpretationsupporting
confidence: 90%
“…This suggests that the use of mobile technology has a statistically significant impact on the instructional activities of physics instructors and students during the COVID-19 lockout, as well as students' attitudes toward academic activity. The findings are consistent with those of Alzougool and Almansour [17] , who discovered that using a mobile device benefited both students and instructors. The findings were also consistent with those of Iqbal and Bhatti [18] and Onyema et al [19] , who discovered that mobile phones have interesting features that are appealing to learning.…”
Section: Regression Analysis and Interpretationsupporting
confidence: 90%
“…One of the significant findings from the survey was the substantial increase in smartphone ownership among students. Similarly, a study by Alzougool and Almansour (2017) found that (99 percent) of university students in Kuwait owned a smartphone. Table I provides more detailed information on mobile device use.…”
Section: Mobile Device Usementioning
confidence: 91%
“…Kuwaiti students interact with mobile phones. In Kuwait, research shows a clear pattern where students use their smartphones most heavily at home, but also while traveling, on campus, and during leisure time [25]. This paints a picture of the mobile phone's deep integration into the fabric of students' lives, effortlessly spanning both work and relaxation.…”
Section: Studies Within the Gulf Region Offer A Window Into Howmentioning
confidence: 99%